Catalyst Screening by Electrospray Ionization Tandem Mass Spectrometry: Hofmann Carbenes for Olefin Metathesis - Volland, Martin August Otfried; Adlhart, Christian; Kiener, Christoph Alexander; Chen, Peter; Hofmann, Peter (Chemistry : a European journal, 2001)
A new screening methodology, which combines in situ synthesis of complexes with an assay by electrospray ionization tandem mass spectrometry (ESI‐MS), is introduced in order to investigate highly active, cationic ruthenium–carbene catalysts in ring‐opening metathesis polymerization (ROMP). The parameter space, whic is defined by systematic variation of four structural features of the catalyst [{R2P(CH2)nPR2‐κ2P}XRu=CHR′]+ (the halogen ligand, the diphosphane bite‐angle, the steric bulk of the phosphane, and the carbene ligand) and the variation of the metathesis substrate, is mapped out. Chloride as the anionic ligand X, a small chelating angle (n=1), and reduced steric demand of the substituents R (Cy versus tBu) lead to the most reactive complex in acyclic olefin metathesis, whereas variation of the carbene moiety CHR′ has only a modest influence. The overall rate in the gas phase depends on the π‐complex preequilibrium and metallacyclobutane formation, which was found to be the rate‐determining step. In ROMP reactions backbiting has a profound influence on the overall rate. Moreover, we were able to establish that the reactivity trends determined in the gas phase parallel solution‐phase reactivity. The overall rate in solution is also determined by a favorable dimer/monomer preequilibrium providing the active catalyst by facile dissociation of dicationic, dinuclear catalyst precursors. A new and efficient high‐throughput screening methodology, which combines in situ synthesis of catalysts with an assay by electrospray ionization tandem mass spectrometry (ESI‐MS), is introduced in order to investigate the highly active olefin metathesis ruthenium–carbene catalysts [{R2P(CH2)nPR2‐κ2P}XRu=CHR′]+. A five‐dimensional parameter space was scanned in a total of 1800 experiments (see diagram). The study reveals how structural modifications and the nature of the substrate govern catalyst reactivity towards olefins and uncovers key mechanistic details.